Comparison of Anti-CD3/anti-CD28 Antibodies Combination with Phytohemagglutinin for Stimulating T Lymphocyte Proliferation - Huyen, Le Thi; Hien, Mai Thi; Ha, Nguyen Thi Ngoc; Anh, Pham Tuan; Anh, Bui Viet; Nhung, Hoang Thi My; Hung, Nguyen Xuan; Tu, Nguyen Dac; Dinh Chien, Huynh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 40 No 3, 2024)
It is well known that T lymphocytes play important roles in autoimmune disease and cancer therapies. The activation of CD4 + T cells is crucial in regulating the body's immune system. Therefore, T lymphocyte culture expansion is necessary for T cell therapy research and medical applications. N umerous   methods to stimulate T lymphocytes in vitro have been reported, yet there are no consistent results on the characterization of T lymphocytes after stimulation. In this study, we investigated the proliferation and surface markers expression (HLA-DR and CD25) of T lymphocytes and CD4 + T cells from peripheral blood after stimulation. Two activation methods were used in this study, including stimulation with an anti-CD3 antibody combined with an anti-CD8 antibody (anti-CD3/CD28) and stimulation with phytohemagglutinin (PHA). The results showed that after 03 days of stimulation with anti-CD3/CD28 antibodies, T lymphocytes formed a homogeneous population and obtained higher rates of viability . However, a greater proliferation index was observed in PHA-stimulated cells. Additionally, CD4 + T cells expressed more HLA-DR and CD25 surface markers when stimulated with PHA. In conclusion, both methods showed outstanding efficacies. Hence the two approaches should be selected in different circumstances based on the purpose of the studies.